PERFORMANCE STUDY OF UNBALANCED LOAD ON OPEN DELTA TRANSFORMERS - Pelpinus Sinay (International Journal Multidisciplinary Science, 2023)
A transformer is a device that can transfer (transmit) and change electrical energy from one electrical circuit to another with the same frequency based on the principle of electromagnetic induction. The transformer that will be used in this research is a three-phase open delta connection transformer, which is connected to a delta connected load. If one of the three phase windings in the delta connection transformer is damaged, then the remaining two windings can be implemented or designed into three phase open delta connections, which can be used to distribute three phase electrical power to the load. The performance of the unbalanced load influence on the open delta transformer, when it is loaded with an unbalanced load that is not the same size on each phase, causes an increase in current on each phase, resulting in an increase in the input power absorbed by the unbalanced load resulting in power loss. larger (losses) with reduced efficiency. The aim of the research is to study the performance of unbalanced loads on open delta transformers and the research method is an experimental method in the laboratory, which includes testing on three-phase open delta transformers in unbalanced load conditions. The measurement results show that there are differences in performance (output results) in the influence of unbalanced loads between the average current and losses and the efficiency of the open delta transformer.